Pengaruh E-Wom Terhadap Customer Engagement Pelanggan Osbond Gym Bekasi Dalam Penerapan Protokol Kesehatan Covid-19 - Vendy Octavian; Wulan Purnama Sari (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
Electronic word of mouth is a message or information that comes from personal experience or consumer opinion on a product or service and is spread by word of mouth via the internet media. High electronic word of mouth can create customer engagement. Customer engagement is an attitude towards a brand or company, which involves active consumer commitment through online media in the form of word-of-mouth activities, providing reviews, recommendations, and blogging that is driven by motivation. This study aims to measure the effect of electronic word of mouth on customer engagement at Osbond Gym Bekasi. This research uses quantitative techniques with a survey method. Primary data were collected through distributing questionnaires to 85 respondents who are customers of Osbond Gym Bekasi. Data analysis used the Statistical Package for the Social Sciences with the SPSS for Windows 25 application. Based on the research results, it is known that there is a positive influence between electronic word of mouth on customer engagement. Electronic word of mouth has an effect of 69.7% on customer engagement, while 30.3% is another factorElectronic word of mouth adalah suatu pesan atau informasi yang berasal dari pengalaman pribadi atau opini konsumen akan suatu produk atau jasa dan disebarkan dari mulut ke mulut melalui media internet. Electronic word of mouth yang tinggi dapat menciptakan customer engagement. Customer engagement merupakan suatu sikap terhadap merek atau perusahaan, yang melibatkan komitmen konsumen secara aktif melalui media online yang berupa aktivitas word-of-mouth, memberikan review, rekomendasi, dan blogging yang didorong oleh suatu motivasi. Penelitian ini bertujuan untuk mengukur pengaruh electronic word of mouth terhadap customer engagement di Osbond Gym Bekasi. Penelitian ini menggunakan teknik kuantitatif dengan metode survei. Data primer dikumpulkan melalui penyebaran kuesioner kepada 85 responden yang merupakan pelanggan dari Osbond Gym Bekasi. Analisis data menggunakan Statistical Package for the Social Sciences dengan aplikasi SPSS